2019
DOI: 10.1111/jfpp.14184
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of coconut–flaxseed balls enriched with chiaseeds

Abstract: Flaxseed composite flour enriched with 5% coconut, 5%, 10%, 15%, 20%, and 25% chiaseeds was used for the formulation of coconut–flaxseed balls. The chiaseeds enrichment effect was evaluated for physicochemical and sensory properties of coconut–flaxseed balls. Bioactive phenolics content and antioxidant activity were also determined. Addition of chiaseeds increased the ash up to 4.1%, crude fiber up to 33%, and nitrogen‐free extract up to 12.9% in the product along with improving the mineral profile for iron, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Each value represents the mean of three replicates ±SD. Mean values with the different letters in the same column mean significantly different at p≤0.05.Similar studies explained the nutritional value for wheat flour fortified with chia seeds(Hafeez et al, 2019 andGuiotto et al, 2020). Results are agreed with (Alamri, 2020) reported that protein content in each 100 g chia seed was around…”
supporting
confidence: 87%
“…Each value represents the mean of three replicates ±SD. Mean values with the different letters in the same column mean significantly different at p≤0.05.Similar studies explained the nutritional value for wheat flour fortified with chia seeds(Hafeez et al, 2019 andGuiotto et al, 2020). Results are agreed with (Alamri, 2020) reported that protein content in each 100 g chia seed was around…”
supporting
confidence: 87%